The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/smr.1992
|View full text |Cite
|
Sign up to set email alerts
|

Concrete hyperheuristic framework for test case prioritization

Abstract: Test case prioritization (TCP), which aims to find the optimal test case execution sequences for specific testing objects, has been widely used in regression testing. A wide variety of search methodologies and algorithms have been proposed to optimize test case execution sequences, namely, search‐based TCP. However, different algorithms perform differently and have different implementation costs and specific situations where an algorithm usually performs with high effectiveness and efficiency. When facing a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 69 publications
(91 reference statements)
0
18
0
Order By: Relevance
“…This study reported an average APSC of 96.34% for statement coverage and 738.87 as an average of the EET when 100% statement coverage was achieved for several iterations compared to 18734.4 seconds of the average execution time with reduction of around 96% of the actual time. This study argues that the execution time for this framework is always shorter than the multi-objective PSO algorithm [7].…”
Section: B Multi-objective Frameworkmentioning
confidence: 92%
See 3 more Smart Citations
“…This study reported an average APSC of 96.34% for statement coverage and 738.87 as an average of the EET when 100% statement coverage was achieved for several iterations compared to 18734.4 seconds of the average execution time with reduction of around 96% of the actual time. This study argues that the execution time for this framework is always shorter than the multi-objective PSO algorithm [7].…”
Section: B Multi-objective Frameworkmentioning
confidence: 92%
“…Bian, Li, Gao and Zhao [7] proposed a concrete hyper-heuristic framework for prioritizing test cases. The main purpose of this framework is to select, among several algorithms in the repository, the appropriate algorithm for different TCP scenarios.…”
Section: B Multi-objective Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…TCP technique is proposed to define the execution order of test cases in a test suite according to given criteria. In other words, TCP is aimed to find an optimal text case execution to achieve specific testing objectives [116]. Maximum faults can be revealed from the execution of reordered test cases.…”
Section: Introductionmentioning
confidence: 99%